DDX10 promotes human lung carcinoma proliferation by U3 small nucleolar ribonucleoprotein IMP4. Issue 12 (11th May 2021) - Liu, Chunquan; Tang, Jizheng; Duan, Xinchun; Du, Yanlin; Wang, Xiaoran; Cui, Yong
Abstract: Background: Lung cancer is a common tumor and a leading cause of death worldwide. DEAD/H box RNA helicases (DDX) include several family members which regulate mRNA translation in cancer cells. In this study, we demonstrated that DEAD/H box RNA helicase 10 (DDX10) was significantly upregulated in lung cancer tissues compared with adjacent nontumor tissues. Methods: DDX10 expression was knocked down with shRNA in order to investigate the impact on A549 lung cancer cell growth and related molecular mechanisms in vitro and in vivo. DDX10 expression in lung cancer was assessed using online databases and patient samples. Results: DDX10 knockdown significantly inhibited the proliferation of lung cancer cells in vitro and in vivo. Furthermore, the bioinformatic tool indicated the putative downstream protein U3 small nucleolar ribonucleoprotein 4 (IMP4). Our data showed a positive correlation between IMP4 and DDX10. We found that IMP4 overexpression could reverse the effect of DDX10 knockdown on the proliferation and apoptosis of A549 cells. Conclusions: The findings of this study suggest that DDX10/IMP4 might be a novel target for lung cancer diagnosis and treatment. Abstract : DEAD/H box RNA helicase 10 (DDX10) is significantly upregulated in lung cancer. DDX10 knockdown significantly inhibited the proliferation of lung cancer cells in vitro and in vivo. IMP4 overexpression could reverse the effect of DDX10 knockdown on the proliferation and apoptosis of lung cancer cells.